Die Lösung einer elliptischen Gleichungsystem - Šileris, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. В. Шилeрис. Решение системы уравнений эллиптического типаV. Šileris. Elipsinio tipo lygčių sistemos sprendimas